An Update on Situation and Management Challenges of Recurrent Ebolavirus Disease in the Democratic Republic of Congo - Inungu, Joseph; Iheduru-Anderson, Kechi; Odio, Ossam J. (Recent Updates in Disease and Health Research Vol. 6, 2024)
The Democratic Republic of Congo (DRC) is facing its tenth Ebolavirus (EVD) outbreak since August 2018. Ebola virus disease is a rare but deadly disease in people and non-human primates. The current Ebolavirus disease (EVD) outbreak in the provinces of North Kivu and Ituri is the tenth outbreak affecting the Democratic Republic of Congo (DRC); the first outbreak occurring in a war context, and the second most deadly Ebolavirus outbreak on record following the 2014 outbreak in West Africa. The primary aim of the study is to give an update on the situation of recurrent Ebola virus disease in the Democratic Republic of Congo and provide insight into the challenges associated with managing and controlling the disease. The DRC government’s response consisted of applying a package of interventions including detection and rapid isolation of cases, contact tracing, population mapping, and identification of high-risk areas to inform a coordinated effort. The coordinated effort was to screen, ring vaccinate, and conduct laboratory diagnoses using GeneXpert (Cepheid) polymerase chain reaction. The effort also included ensuring safe and dignified burials and promoting risk communication, community engagement, and social mobilization. Following the adoption of the “Monitored Emergency Use of Unregistered Products Protocol,” a randomized controlled trial of four investigational treatments (mAb114, ZMapp, and REGN- EB3 and Remdesivir) was carried out with all consenting patients with laboratory-confirmed EVD. REGN-EB3 and mAb114 showed promise as treatments for EVD. In addition, one investigational vaccine (rVSV-ZEBOV-GP) was used first, followed by a second prophylactic vaccine (Ad26.ZEBOV/MVA-BN-Filo) to reinforce the prevention. Although the provision of clinical supportive care remains the cornerstone of EVD outbreak management, the DRC response faced daunting challenges including general insecurity, violence and community resistance, appalling poverty, and entrenched distrust of authority. Ebolavirus remains a public health threat. Fully curative treatment is unlikely to be a game-changer given the settings of transmission, zoonotic nature, limits of the effectiveness of any therapeutic intervention, and timing of presentation.